2005
DOI: 10.1590/s1516-35982005000700029
|View full text |Cite
|
Sign up to set email alerts
|

Fatores determinantes do desempenho reprodutivo de vacas Nelore na região dos Cerrados do Brasil Central

Abstract: RESUMO -Avaliou-se, durante quatro estações de monta (1/11 a 31/1 do ano seguinte), o efeito da ordem de parto (OP) e da condição corporal (CC), segundo escala de 1 (magra) a 5 (gorda), sobre o desempenho reprodutivo de 468 fêmeas Nelore, sendo 391 vacas multíparas e 77 primíparas, em pastagem de Brachiaria decumbens Stapf, na região dos Cerrados, no Brasil Central. A OP teve efeito quadrático na taxa de prenhez (TP). Vacas OP1 apresentaram TP de 69%, OP5 a OP8 de 90%, com declínio gradual até 80% de prenhez n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
1
14
0
9
Order By: Relevance
“…Pregnancy rates were not different among systems possibly due to the low number of experimental animals per management system. However, under commercial systems, or when the effect of year on the same commercial herd is considered (Vieira et al, 2005b), pregnancy rates are 10 to 13% higher in cows with calves, which affects outcome rates and selection opportunities in subsequent years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy rates were not different among systems possibly due to the low number of experimental animals per management system. However, under commercial systems, or when the effect of year on the same commercial herd is considered (Vieira et al, 2005b), pregnancy rates are 10 to 13% higher in cows with calves, which affects outcome rates and selection opportunities in subsequent years.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, high pregnancy rates are difficult to obtain in primiparous cows, and therefore they should be managed separately from mature cows, and be fed at higher nutritional levels. According to Vieira et al (2005b), first-and second-calf cows with calves present the lowest pregnancy rates in cow herds.…”
Section: Introductionmentioning
confidence: 99%
“…O terço final da gestação em fêmeas bovinas é o período de maior restrição alimentar Vieira et al, 2005). Para a novilha prenhe aos 13/15 meses de idade manter-se em gestação, parir em condições de criar bem o bezerro e conceber no período reprodutivo subseqüente, deve ter bom ganho de peso durante a gestação.…”
unclassified
“…Vieira et al (2005), working with five 20-day calving subseasons, found that pregnancy rates were higher than 90% when calvings occurred during the first sub-season (from August 12 th to September 1 st ) and 79.9% for calving occurring during the last sub-season (from October 31 st to November 20 th ). This demonstrates that calving date and season strongly influence reproductive performance.…”
Section: Resultsmentioning
confidence: 99%